SIFAT FISIK MEKANIK PAPAN PARTIKEL DARI AMPAS SAGU (Metroxylon sp) BERDASARKAN UKURAN PARTIKEL DAN PERBANDINGAN ASAM SITRAT-SUKROSA - Wiwit, .; Setyawati, Dina; Yani, Ahmad; Nurhaida, . (Universitas Tanjungpura, 2019)
The manufacture of particleboards from dregs of sago and natural adhesives of citric-sucrose acid has not been widely reported. The aim of this research to examine the physical and mechanical properties of particleboard from dregs of sago based on particle size and the ratio of citric-sucrose. The dregs of sago used is 8-10 mesh and 20-40 mesh. Natural adhesive is used 20% of the dry weight dregs of sago. The ratio of citric acid-sucrose used varies 0/100, 25/75, 50/50, 75/25, 100/0. The particleboard is made manually consisting of 3 layers (face, core, back) were manufactured in 30 cm x 30 cm x 1 cm, and the target of density was 0,7 g/cm3. The pressing at a temperature of 180oC for 15 minutes, and pressure of 20 kg/cm2. The physical and mechanical Â properties of particleboard were tested in accordance to standard JIS A 5908-2003 Type 8. The results showed particleboard that physical properties meets the standards is density, moisture content, and thickness development. The particleboard dregs of sago with ratio citric acid-sucrose 25/75 was able to provide the best results to meet the standards of JIS A 5908-2003 Type 8 for density values of 0,7532 g/cm3, moisture content of 8,6725%, thickness of Â development 8,0756%.Keywords: citric acid-sucrose , dregs of sago, particleboard, particle size